Keterampilan Menulis Puisi dengan Penguatan Karakter Melalui Teknik Sanggam Riska - Supriyanto Supriyanto (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
This article is based on good practice on how to integrate strengthening character education through the “Sanggam Riska” technique with the aim of improving poetry writing skills for grade VIII junior high school students. It was found that there were indications of a student's lack of courtesy, both to fellow students and to the teacher. The